2014
DOI: 10.1136/heartjnl-2013-304912
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after final kissing balloon inflation compared with no final kissing balloon inflation in bifurcation lesions treated with a dedicated coronary bifurcation stent

Abstract: A lower cardiac death rate was observed in patients in whom FKBI was performed compared with a selection of patients in whom FKBI could not be performed, probably explained by an unbalance in the baseline risk profile of the patients. No differences were observed regarding the other clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…These results are in agreement with our previous clinical trial, POLBOS I, in which application of FKB and POT was associated with lower LLL and better clinical outcomes [ 4 ]. These findings were confirmed in other studies, also in trials with other dedicated bifurcation stents [ 18 20 ].…”
Section: Discussionsupporting
confidence: 86%
“…These results are in agreement with our previous clinical trial, POLBOS I, in which application of FKB and POT was associated with lower LLL and better clinical outcomes [ 4 ]. These findings were confirmed in other studies, also in trials with other dedicated bifurcation stents [ 18 20 ].…”
Section: Discussionsupporting
confidence: 86%
“…The administration of statin was related to dyslipidaemia and stent length was related to lesion length. Several factors influence the kissing balloon technique technique, including operator’s proficiency, CKD, ST segment elevation myocardial infarction as an indication for PCI, a narrow bifurcation angle and stent platforms 17 . Therefore, we excluded statin administration, stent length and kissing balloon technique from the multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of BA on final kissing balloon inflation (FKBI) remained a question to be clarified. Grundeken et al reported that narrow angle B was significantly associated with FKBI failure. However, Chen et al and Dzavik et al found that angle B did not necessarily affect the performance of FKBI.…”
Section: Introductionmentioning
confidence: 99%